(untitled) (Vallis Aurea, 2016)
Pozega-Slavonia County has a long tradition of viticulture and oenology at which it becomes ever more recognizable. Although this is the economic segment of high importance for the local economy and regional development this study has shown that there is low percentage of representation in relation to the total agriculture potential of the county. In Republic of Croatia there are counties with higher number of vineyards planted (per unit of the area) vine production in Pozega-Slavonia County shows a greater amount of products of higher quality. With the analysis of the available statistical data it has been noticed that there is room for growth of this market segment and potential of multiplier effects in the development of the local economy with additional uprising in this sector. The target of the research has been gaining an insight into the current state of the agricultural sector of Pozega-Slavonia County emphasizing on production of fresh grapes and wine. Goal was to gain perspective in correlation between viticulture and winemaking with complete agriculture situation in Pozega-Slavonia County and to compare this branch with other counties in Croatia.